2014
DOI: 10.1590/1807-55092014000400641
|View full text |Cite
|
Sign up to set email alerts
|

Visuomotor memory in elderly: effect of a physical exercise program

Abstract: Memory, namely visuomotor memory, is one of the most essential cognitive functions in elder's life. Among others, regular exercise seems to be an important factor in counteracting age-related-cognitive skills changes and thus prevent memory loss. However, in spite of the importance of visuomotor memory, the results of the scarce studies concerning the infl uence of exercise on this capacity are contradictory. The aim of this study was to investigate the effect of physical exercise (PE) in visuomotor memory (VM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 42 publications
(35 reference statements)
0
1
0
1
Order By: Relevance
“…In Silva et al [27] study in order to investigate the effect of a physical exercise program (SP), the memory has been identified that the EP had a positive effect on the memory of the elderly regardless of the variables sex and age.…”
Section: Discussionmentioning
confidence: 99%
“…In Silva et al [27] study in order to investigate the effect of a physical exercise program (SP), the memory has been identified that the EP had a positive effect on the memory of the elderly regardless of the variables sex and age.…”
Section: Discussionmentioning
confidence: 99%
“…O aumento do número de anos com vida saudável e a diminuição do total de anos com doença e incapacidade parecem constituir a melhor estratégia para travar a subida de custos com a saúde. Iniciativas que envolvam o idoso em atividades físicas e de interação social, no quadro de redes de suporte social informal ou formal, parecem ser determinantes para a revitalização das independências funcional, cognitiva e social (Fechine, Trompieri 2011;Fechine, Trompieri 2012;, Fechine et al 2013bSilva et al 2014).…”
Section: Introductionunclassified